Case Studies in Teaching Systems Thinking. Issue 6 (2016) - Benedek, A.; Horváth Cz., J.
Abstract: The education of systems thinking needs prepared teachers, descriptive examples and case studies easy to understand by the students. Why could not this latter be collected and "explored" by the students? These small case studies might make the learning resources more interesting and more personal, and so studying might become more effective. Our paper deals with the questions of seeking a pedagogical paradigm related to the 'Systems and control are all around us' approach. During our endeavours made to develop Open Education Resources (OER) within the frames of our experiment implemented in 2015, we found that student participation offered great potentials in relation to the content and the methodology, as well. Traditional teaching relying upon school books can considerably be modernized by the IT solutions applied during the experimental development of learning materials for vocational education and training (Systems in VET). By introducing the experiences of the experimental phase, this article summarizes the steps made towards establishing a new form of system teaching based on case studies and applicable in VET in a wider range.